Non-Linear Market Demand and Capital Accumulation in A Differential Oligopoly Game - Luca Lambertini; Roberto Cellini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2000)
We investigate a differential oligopoly game where firms compete in account Market whose demand function is always downward sloping but can take any degree of curvature. There exist two economically meaningful saddle points, one dictated by demand conditions, the other by the Ramsey rule. In steady state, optimal capital is non-decreasing in market size. Then we show that the socially efficient output is independent of the curvature of market demand. This entails that the welfare loss associated to the Cournot equilibrium decreases as market size increases.
Keywords: 330